Ação de fertilizantes orgânicos sob Pratylenchus brachyurus e Meloidogyne javanica em plantas de soja e tomate - Dossin, Mariana Ferneda (2020)
There is little research information on the agronomic response to the application of organic compounds as organic fertilizers in agriculture and in the effectiveness of crop development. The elucidation of the action of these compounds as potential agents to suppress phytopathogens, such as nematodes, is of great importance. Thus, the objective of this work was to obtain information about the action of organic fertilizers in the development of soybean and tomato plants, and their action in the suppression of the plant parasitic nematodes Pratylenchus brachyurus and Meloidogyne javanica. Three studies were carried out. The main objective of Study 1 was to characterize the action of different organic fertilizers in suppressing the P. brachyurus in the development of soybean plants. The residues of cattle manure (CM), cattle compost (CC), cattle vermicompost (CV) and slaughterhouse swine compost (SSC) were tested for mineral fertilization in a greenhouse. The action of organic fertilizers was evaluated in relation to the presence and reproduction of P. brachyurus in the soybean crop and the production of the crop's biomass. The Study II investigated the effect of the cattle compost compound and the slaughterhouse swine compost on the population of M. javanica on the soil and on the damage to tomato roots. And, the Study III evaluated and characterized the action of organic fertilizers on the physiological parameters, gas exchange and chlorophyll a fluorescence of soybean plants. For that, two organic composts were used, cattle compost (CC) and slaughterhouse swine compost (SSC) in relation to mineral fertilization. In addition evaluated to dry matter of shoots and roots, in three stages of development of soybean plants, V4, R2 and R5. The main results, it can be highlighted that the organic fertilizers tested in all studies, promoted increases in dry matter of shoots and roots when compared to mineral fertilizer, being considered good sources of nutrients and contributed positively to the development of plants. For suppression of the P. brachyurus, only fertilizers made from cattle manure based, cattle compost and cattle vermicompost showed positive results. In the suppression of the M. javanica, there was no suppression by organic fertilizers tested in tomato plants.